BUDGETING AND FORECASTING IN MARKETING COMMUNICATIONS: AN ACCOUNTING PERSPECTIVE - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Budgeting and forecasting are integral components in planning and managing marketing communications from an accounting perspective. This paper discusses the importance of applying accounting principles in the budgeting and forecasting process to ensure sound financial management and data-backed decision-making. The accounting approach emphasises accurate recording of marketing expenditure, proper cost allocation, profitability analysis, ROI evaluation, and measurement of marketing performance using financial metrics. In a dynamic business environment, a flexible and adaptive approach to budgeting and forecasting is becoming increasingly important. Close collaboration between marketing and finance departments is also crucial to ensure strategy alignment and smooth execution. By combining marketing insights with accounting disciplines, companies can optimise marketing spend, increase accountability, and drive profitable growth in the long run.